Advancing equity in cancer research through principled partnership: stakeholder engagement practices in The Social Interventions for Support during Treatment for Endometrial cancer and Recurrence (SISTER) Study - Julianna G. Alson; Kemi M. Doll; Bridgette H. Hempstead; Lisa Barr; Danielle C. Lavallee; Liz Sage; Adrienne Moore; Scott D. Ramsey; Erika M. Wolff; Bryan A. Comstock; Sarah E. Monsell; Ronit Katz; et al. (Research Involvement and Engagement)
Abstract Background In cancer, lack of social support is associated with reduced survival. Peer support interventions have reduced social isolation among Black women with cancer but have yet to be adapted for Black people diagnosed with endometrial cancer – a growing, high-need demographic that has been historically excluded from community-engaged research. Our research team at the University of Washington addressed this gap by working within an established community partnership to develop a pragmatic randomized controlled trial to adapt and test social support interventions among Black women with EC – the Social Interventions for Support during Treatment of Endometrial Cancer and Recurrence (SISTER) Study. The goal of this commentary is to describe the stakeholder engagement practices used in the conceptualization and start-up of the SISTER Study. Main Text The research team, including Black endometrial cancer survivors, developed a grant proposal, grounded in engagement values derived from the Patient-Centered Outcomes Research Institute® and the Public Health Critical Race Praxis. The team implemented values-aligned stakeholder engagement activities, including the creation of an advisory board charter, structuring meetings and roles, incorporating stakeholder input into study material and protocols, establishing an external advisory board, and developing an engagement evaluation plan. Overall, we learned that it is possible to design and operationalize a community-engaged pragmatic randomized controlled trial in alignment with a racial equity social justice research methodology and patient-centered outcomes research engagement practices. We describe other lessons learned, including operational challenges to implementing our engagement practices and our approaches to addressing these challenges, and promising practices to replicate in future studies or partnerships. Conclusion The SISTER Study is an example of establishing principled methods of stakeholder engagement within an area of study and population that has been underrepresented in stakeholder-engaged research. The engagement practices within the SISTER Study can inform community-academic partnership practices in health equity research.